E-027 Robotics and artificial intelligence in endovascular neurosurgery. (23rd July 2022) - Bravo, J; Wali, A; Gopesh, T; Hirshman, B; Steinberg, J; Yan, B; Pannell, J; Norbash, A; Friend, J; Santiago-Dieppa, D; Khalessi, A
Abstract : Introduction: The use of artificial intelligence and robotics in endovascular neurosurgery promises to transform neurovascular care. We present a review of the recently published neurosurgical literature on artificial intelligence and robotics in endovascular neurosurgery to provide insights on the current advances and applications of this technology. Methods: The PubMed database was searched for ('neurosurgery' OR 'endovascular' OR 'interventional') AND ('Robotics' OR 'Artificial intelligence') between January 2016 and August 2021. A total of 1296 articles were identified, and after applying inclusion and exclusion criteria, 38 manuscripts were selected for review and analysis. These manuscripts were divided into four categories: 1) robotics and AI for diagnosis of cerebrovascular pathology, 2) robotics and AI for treatment of cerebrovascular pathology, 3) robotics and AI for training in neuroendovascular procedures, and 4) robotics and AI for clinical outcome optimization. Results: The 38 articles presented include 23 articles on AI-based diagnosis of cerebrovascular disease, 10 articles on AI-based treatment of cerebrovascular disease, 2 articles on AI-based training techniques for neuroendovascular procedures, and 3 articles reporting AI prediction models of clinical outcomes in vascular disorders of the brain. Innovation with robotics and AI focus on diagnostic efficiency, optimizing treatment and interventional procedures, improving physician procedural performance, and predicting clinical outcomes with the use of artificial intelligence and robotics. Experimental studies with robotic systems have demonstrated safety and efficacy in treating cerebrovascular disorders, and novel microcatheterization techniques may permit access to deeper brain regions. Other studies show that pre-procedural simulations increase overall physician performance. Artificial intelligence also shows superiority over existing statistical tools in predicting clinical outcomes. Conclusion: The recent advances and current usage of robotics and AI in the endovascular neurosurgery field suggest that the collaboration between physician and machine has a bright future for the improvement of patient care. The aim of this work is to equip the medical readership, in particular the neurosurgical specialty, with tools to better understand and apply findings from research on artificial intelligence and robotics in endovascular neurosurgery. Disclosures: J. Bravo: None. A. Wali: None. T. Gopesh: None. B. Hirshman: None. J. Steinberg: None. B. Yan: None. J. Pannell: None. A. Norbash: None. J. Friend: None. D. Santiago-Dieppa: None. A. Khalessi: None.